The complete mitochondrial genome of the freshwater crab Sinolapotamon patellifer (Decapoda: Brachyura: Potamoidea) - Ji, Wen-Bin (Mitochondrial DNA B Resour, 2019)
We report the complete mitochondrial genome of Sinolapotamon patellifer for the first time, which is found to be 16,547 base pairs in length, and contains 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA), and one non-coding AT-rich region known as the D-loop. In addition, the mitogenome has 17 intergenic regions ranging from 1 to 1512 bp in length. The mitochondrial genome of S. patellifer is the first mitochondrial genome under the genus Sinolapamon, providing DNA data for species identification, enriching the species diversity of Brachyura, and providing a basis for further studies on population genetics and phylogenetics.